Gene aberrations for precision medicine against lung adenocarcinoma - Saito, Motonobu (Cancer Sci, 2016)
Lung adenocarcinoma (LADC), the most frequent histological type of lung cancer, is often triggered by an aberration in a driver oncogene in tumor cells. Examples of such aberrations are EGFR mutation and ALK fusion. Lung adenocarcinoma harboring such mutations can be treated with anticancer drugs that target the aberrant gene products. Additional oncogene aberrations, including RET,ROS1, and NRG1 fusions, skipping of exon 14 of MET, and mutations in BRAF,HER2,NF1, and MEK1, were recently added to the list of such “druggable” driver oncogene aberrations, and their responses to targeted therapies are currently being evaluated in clinical trials. However, approximately 30% and 50% of LADCs in patients in Japan and Europe/USA, respectively, lack the driver oncogene aberrations listed above. Therefore, novel therapeutic strategies, such as those that exploit the vulnerabilities of cancer cells with non‐oncogene aberrations, are urgently required. This review summarizes the current status of research on precision medicine against LADC and enumerates the research priorities for the near future.